2011
DOI: 10.1175/jas-d-11-07.1
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Sudden Warmings as Self-Tuning Resonances. Part I: Vortex Splitting Events

Abstract: The fundamental dynamics of ''vortex splitting'' stratospheric sudden warmings (SSWs), which are known to be predominantly barotropic in nature, are reexamined using an idealized single-layer f-plane model of the polar vortex. The aim is to elucidate the conditions under which a stationary topographic forcing causes the model vortex to split, and to express the splitting condition as a function of the model parameters determining the topography and circulation.For a specified topographic forcing profile the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 38 publications
10
105
0
Order By: Relevance
“…The fact that there is a multiday time lag between when the vortex begins to split and when the largest wave fluxes appear seems to support the contention put forth by Matthewman and Esler (2011) that split-type SSWs are characterized by nonlinear wave growth (i.e., a wave-amplitude bifurcation) rather than anomalous tropospheric wave forcing. The key but subtle implication to this idea is that, while an SSW is indeed characterized by a large-amplitude wave-2 vortex event, the anomalously large wave fluxes themselves are the result, not the cause, of the SSW.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…The fact that there is a multiday time lag between when the vortex begins to split and when the largest wave fluxes appear seems to support the contention put forth by Matthewman and Esler (2011) that split-type SSWs are characterized by nonlinear wave growth (i.e., a wave-amplitude bifurcation) rather than anomalous tropospheric wave forcing. The key but subtle implication to this idea is that, while an SSW is indeed characterized by a large-amplitude wave-2 vortex event, the anomalously large wave fluxes themselves are the result, not the cause, of the SSW.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast to the concept of anomalous wavetriggered SSWs, recent theoretical SSW studies have suggested that anomalous tropospheric upward wave fluxes are not necessary for triggering an SSW (Esler and Scott 2005;Scott and Polvani 2006;Matthewman and Esler 2011;Esler and Matthewman 2011). These studies suggest that the explosive growth of wave amplitude that occurs during an SSW is instead representative of nonlinear resonance that is triggered by the modulation of key geometric vortex parameters that are defined based on whether a split or displacement-type warming (Charlton and Polvani 2007) is under consideration.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations